Nutrients removal and biomass production from anaerobic digested effluent by microalgae: A review - Li, Gang; Bai, Xue; Li, Huan; Lu, Zhitao; Zhou, Yuguang; Wang, Yingkuan; Cao, Jinxin; Huang, Zhigang (International Journal of Agricultural and Biological Engineering, 2019)
This article summarizes the recent progress of nutrient removal from wastewater via microalgae. Removal of nitrogen and phosphorous compounds from wastewater are of great importance, while those compounds are suitable for growth of some microalgae species. Such a combination provides more opportunities for anaerobic digestion facilities, which are producing large amount of wastewater with high nitrogen and phosphorous contents. However, in order to optimize and maximize the performance and durability of the nutrient removal process, it is suggested that the basic principles about nitrogen and phosphorous migration should be investigated thoroughly, especially from the fundamentals of substance transfer mechanism between water environment and algal cells. Keywords: microalgae, biomass accumulation, nutrient removal, anaerobic digested effluent (ADE), pollution control DOI: 10.25165/j.ijabe.20191205.3630 Citation: Li G, Bai X, Li H, Lu Z T, Zhou Y G, Wang Y K, et al. Nutrients removal and biomass production from anaerobic digested effluent by microalgae: A review. Int J Agric & Biol Eng, 2019; 12(5): 8–13.